Qualidade e composição química da carne de bovinos de corte inteiros ou castrados de diferentes grupos genéticos Charolês x Nelore - Vaz, F. N.; Restle, J.; Feijo, GLD; Brondani, I. L.; Rosa, JRP; dos Santos, A. P. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2001)
Seventy beef males of three breeding systems (BS), straightbreds Charolais (Ch) and Nellore (Ne), G1 crossbreds: 1/2 Ch + 1/2 Ne (1/2 Ch) and 1/2 Ne + 1/2 Ch (1/2 Ne) and G2 crossbreds: 3/4 Ch + 1/4 Ne (3/4 Ch) and 3/4 Ne + 1/4 Ch (3/4 Ne) were used. The number of animals by genetic group was, respectively, 15, 12,8, 12,14 and 9. Thirty-five males were castrated (C) at seven months and 35 were kept intact (1). The animals were feedlot finished from 20 to 24 months. The longissimus dorsi muscle was used for the meat evaluation. No significant interaction was observed between genetic composition and sexual condition, for the variables studied. The I males displayed meat with darker color (3.05 vs. 3.78 points) with less amount of marbling (4.26 vs. 5.75 points) and less amount of ether extract (1.73 vs. 2.88%). However they presented larger (66.03 vs. 60.50 cm(2)) longissimus dorsi area and meat with better palatability, juiciness and tenderness. Ch animals had larger longissimus dorsi than the Ne. In the G I group, the 1/2 Ch meat showed larger amount of marbling and ether extract and less cooking losses than the 1/2 Ne meat. Between G2 animals, the 3/4 Ne showed meat with larger thawing losses and larger amount of ether extract. In G1 animals meat, the heterosis level reached 18.54% for longissimus dorsiarea, 28.10% for ether extract and 64.01% for amount of marbling. In G2, the heterosis was -17.30% for lean texture and 10.40% for longissimus dorsi area.
Quality and composition of meat from entire or castrated beef cattle from different Charolais x Nellore genetic groups
Keywords: bos indicus; bos taurus; castration; heterosis; marbling; tenderness